Streptamer versus tetramer-based selection of functional cytomegalovirus-specific T cells - Wang, Xin-Chao; Pang, Hua; Xu, Xun; Schmitt, Anita; Freund, Mathias; Schmitt, Michael; Chen, Bao-An (Journal of the Formosan Medical Association, 2013)
Background/Purpose - Cytomegalovirus (CMV) disease constitutes a serious complication after stem cell transplantation and has been treated by adoptive transfer of donor-derived CMV-specific CD8+ T cells. CMV-specific CD8+ T cells were selected by multimers, and the technologies may alter the function of these T cells. Therefore, here we evaluated the impact of multimer reagents on the function of CD8+ T lymphocytes. - Methods - CMV-specific CD8+ T cells were purified from the peripheral blood of donors using tetra- and streptamer technologies. The functional status of purified CMV-specific CD8+ T cells was assessed by multiparametric immunophenotyping and carboxyfluorescein succinimidyl ester proliferation assays as well as by enzyme-linked immunospot assays. - Results - A similar percentage of CMV-specific CD8+ T cells could be purified by both tetra- (90%) and streptamer (92%) technologies. That constitutes a 30- to 50-fold concentration of CMV-specific CD8+CD45RA+CCR7−effector T cells. Selected cells secreted interferon-gamma and granzyme B upon stimulation with CMVpp65 peptide, thus demonstrating their functionality. - Conclusion - Our study demonstrated that both tetra- and streptamer technologies can be used to purify CMV-specific cytotoxic CD8+ T cells for adoptive T-cell transfer. Both multimer technologies did not have any negative influence on the proliferation of selected T cells. Importantly, streptamer technology is available at good manufacturing practice level.